2017
DOI: 10.5897/ijbc2017.1120
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and distribution of African indigenous vegetable species in Uganda

Abstract: African indigenous vegetable species (AIVS) provide a means of livelihood to many urban and periurban dwellers in Uganda. It was thus deemed necessary to understand the existing diversity and distribution of the traditional African vegetable species as a basis for recommending conservation and utilization strategies against biodiversity loss. A field survey was conducted in the four major agroecological zones of Uganda to provide information on a recent abundance of the various AIVS. Results from the survey sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Indigenous leafy vegetables are an important, readily accessible resource that may be used to attain food security and alleviate poverty in rural, semi-urban and urban areas [17][18][19][20]. This is because ILVs have a relatively higher nutritional value compared to exotic vegetables [19].…”
Section: The Role Of Vegetables As Food Security Cropsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indigenous leafy vegetables are an important, readily accessible resource that may be used to attain food security and alleviate poverty in rural, semi-urban and urban areas [17][18][19][20]. This is because ILVs have a relatively higher nutritional value compared to exotic vegetables [19].…”
Section: The Role Of Vegetables As Food Security Cropsmentioning
confidence: 99%
“…Indigenous leafy vegetables are an important, readily accessible resource that may be used to attain food security and alleviate poverty in rural, semi-urban and urban areas [17][18][19][20]. This is because ILVs have a relatively higher nutritional value compared to exotic vegetables [19]. Even though ILVs have not been fully exploited in the quest to achieve food safety and alleviate malnutrition [10], many researchers agree that the vitamins, minerals, phytochemicals with strong antioxidant properties and nutritional (micronutrient) content in ILVs are their most valuable attributes [9,17,18,21].…”
Section: The Role Of Vegetables As Food Security Cropsmentioning
confidence: 99%
“…Data collection was carried out every two weeks on agronomic traits for growth and yield like plant height, number of leaves, leaf area, number of branches per plant, plant vigour, stem girth, total biomass, shoot biomass, root biomass and harvest index as earlier described by Sseremba et al (2017aSseremba et al ( , 2017bSseremba et al ( , 2018 and Nakanwagi et al (2018). The plant height was measured using a meter rule and the stem girth was determined using the thread and meter rule method (Amhakhian et al, 2010).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…In Uganda S. aethiopicum is ranked as the most important local vegetable species (Sseremba et al, 2017a) that is commercially grown, and is allocated larger land acreage than the others (Ssekabembe et al, 2003). It is grown by farmers in all regions with highest production in the central and eastern region due to high marketability (Ssekabembe et al, 2003;Sseremba et al, 2017a) and high nutrient content (Abolusoro et al, 2013). Under good management, farmers growing S. aethiopicum cultivars can get up to 75 leaf bundles of 30 kg each per 100 m 2 meaning that the crop has a yield potential of 225 t ha -1 .…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of the genome structures of 16 solanaceous species revealed that genome-level doubling and large-scale rearrangement events have not occurred in individual species during their independent evolution and that despite the high consistency exhibited between genomes, the phenotypes vary greatly Eggplants (Solanum melongena L.) are the third largest group of solanaceous plants after potatoes and tomatoes (Godfrey et al 2017;Gramazio et al 2017). Together with two African eggplants (Solanum aethiopicum L. and Solanum macrocarpon L.), they constitute an important, economically cultivated group (Jacoby et al 2003;Shackleton et al 2009;Vorontsova et al 2013;Gramazio et al 2016).…”
Section: Introductionmentioning
confidence: 99%